Strategi Guru dalam Mengembangkan Minat Belajar Matematika pada Siswa Kelas II MIN 4 Kebumen - Andrianto Andrianto; Bahrun Ali Murtopo; Oky Ristya Trisnawati (IAINU Kebumen, 2022)
Good learning is learning that can achieve its goals effectively an efficiently. Then aplanning of teaching and learning activities is very important to achieve educationalgoal. However, in the context of the interaction of the teaching and learning process,students sometimes experience tendency to lack enthusiasm and boredom in learning.This study aims to determine the teacher’s strategy in developing students’ interest inlearning mathematics in class and the obstacles faced by teachers when teachingmathematics in grade II Madrasah Ibtidaiyah Negeri 4 Kebumen. This type ofresearch uses qualitative research. The subjeck of this research is the principal, classII teacher and class II students Madrasah Ibtidaiyah Negeri 4 Kebumen. Datacollection techniques using observation, interviews, documentation, and triangulationwhile data analysis techniques using qualitative data analysis, namely data collection,data reduction, data presentation, data verifikasi / drawing conclusions. From theresults of research conducted, it can be concluded that: 1) Teacher’s strategy toincrease interest in learning mathematics in grade II students Madrasah IbtidaiyahNegeri 4 Kebumen are by making ice breaking before learning, using realisticlearning strategies, active learning strategy, individual learning, and group learning,teaching by combining learning methods, use appropriate learning media, and giveawards or prizes to students; 2) The obstacles faced by teachers when teachingmathematics are condition students’ health and fitness, different understandingabilities of students, student attitudes and behavior, unfavorable family and classmateenvironment, and bad environmental conditions